2018
DOI: 10.3390/ijerph15112452
|View full text |Cite
|
Sign up to set email alerts
|

PARS: Using Augmented 360-Degree Panoramas of Reality for Construction Safety Training

Abstract: Improving the hazard-identification skills of construction workers is a vital step towards preventing accidents in the increasingly complex working conditions of construction jobsites. Training the construction workforce to recognize hazards therefore plays a central role in preparing workers to actively understand safety-related risks and make assertive safety decisions. Considering the inadequacies of traditional safety-training methods (e.g., passive lectures, videos, demonstrations), researchers have emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 34 publications
0
53
0
1
Order By: Relevance
“…Researchers have stated that visualization technologies such as VR can efficiently improve current safety training programs and improve workers' hazard recognition skills [32]. Researchers have proposed a platform that utilizes 360-degree panoramas recorded videos from reality and used the videos in VR for construction safety training, and the outcome indicates that the proposed platform will significantly improve workers' hazard identification skills [55].…”
Section: Ar/vr In Aecmentioning
confidence: 99%
“…Researchers have stated that visualization technologies such as VR can efficiently improve current safety training programs and improve workers' hazard recognition skills [32]. Researchers have proposed a platform that utilizes 360-degree panoramas recorded videos from reality and used the videos in VR for construction safety training, and the outcome indicates that the proposed platform will significantly improve workers' hazard identification skills [55].…”
Section: Ar/vr In Aecmentioning
confidence: 99%
“…The preliminary results of this study showed that there were no significant differences between the students who used the 360 VR and those who visited the real site to identify the hazards. In another series of studies, Eiris et al [31,32] developed a hazard identification training and assessment using 360 VR. Users in those studies found 360 VR advantageous for learning about hazard identification.…”
Section: Rq2: Purpose Of Vr-mr Systems For Construction Safetymentioning
confidence: 99%
“…Jeelani et al [6] used panoramic photographs and videos to create an AR training environment to engage and challenge users to properly identify hazards. In similar studies, Pham et al [30] and Eiris et al [31,32] used the power of 360 panoramic VR to create hazard identification training and an assessment environment which engage users in true-to-life simulations of construction jobsites.…”
Section: Rq3: Application Objective Of Vr-mr Systems For Constructionmentioning
confidence: 99%
“…Following this, researches have proved the advantages of VR in providing interactive and experiential learning environments [42,43], which are very important to motivate and engage learners in obtaining hazard knowledge and skills [44]. In an effort to develop VR systems that can provide close-to-reality visibility, recent studies have adopted the 360VP technology, which captures 360 panorama images of real construction sites [17]. The 360VP enhances the real-world learning environment by presenting the dynamic nature of construction sites in reality to improve the hazard investigation knowledge skills of construction students and professionals.…”
Section: Virtual Reality In Construction Hazard Investigationmentioning
confidence: 99%
“…To improve the real-world experience, 360 degree panoramic Virtual Photoreality (360VP) has emerged as a potential pedagogic tool for learners to experience real-word construction workplace environments [17]. The advantage of 360VP is that it provides an immersive learning platform, where the learner can move flexibly and observe the scenes to investigate hazards as they would experience in real construction sites [18].…”
Section: Introductionmentioning
confidence: 99%